Peningkatan Kepercayaan Diri Remaja Melalui Konseling Kelompok - Tina Afiatin; Sri Mulyani Martaniah (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 1998)
Pilot studies revealed that a great deal of psychological problems Inadolescence stem from lack of self-confidence. The studies also found ·that peer groups could function both as social support and as a changeagent tor adolescent. Those findings suggested that group conselingcan be used as an alternative intervention to improve self-confidenceamong adolescents. The present study tested the efficacy of group counseling in in creasing adolescents' self-confidence. Twenty two students of SMA PIRII Yogyakarta who exhibited lack of self-confidence participated in theexperimental and control groups. Each group consisted of 11 students.Self-confidence, self-concept, and self-esteem were the dependentmeasure. Testing were administered 4 times, before treatment, rightafter treatment, one month after treatment and three months after treatment. Behavioral changes were observed through daily record as wellas-observer's rating of subjects behavior during counseling sessions.T-test with gain scores indicated that the Increase in confidencediffered significantly between experimental and control groups (t = 5.01;p < 0.05). Experimental group (( = 28.64) showed higher increase inself-confidence than control group (( = 1.27). The same pattern wasshown for self-concept and self-esteem measures. Behavioral ratingscale Indicated an increase In self-confidence among subjects of experimental group. Key words: Self-Confidence - Adolescence - Group Counseling.